Morbidity and mortality pattern of neonates admitted into a newly established special care baby unit at Asaba specialist hospital, Asaba, Nigeria - Ajaegbu, Obinna C.; Igbosewe, Peace A.; Omoyibo, Efe E.; Okowa, Samuel R.; Rosemary, Ossai R.; Mbagwu, Nkemjika E.; Ajaegbu, Faith N. (International Journal of Contemporary Pediatrics, 2025)
Background: Neonatal morbidity and mortality has remained high in Nigerian and other low and middle-income countries (LMIC) despite numerous advances in newborn care. A periodic review of the common causes of morbidity and mortality will aid in evaluating the practices and improving service delivery. aimed at reducing neonatal morbidity and mortality pattern of neonates admitted into the special care baby unit (SCBU) of Asaba specialist hospital, Delta state, Nigeria. Methods: This was a 3-year retrospective study, carried out at the SCBU of Asaba specialist Hospital, Asaba, between January 2021 and December 2023. Factors including age, sex, weight, diagnosis and outcome were studied. Results: A total of 1,604 neonates were admitted and managed in the SCBU during the period under review with a female to male ratio of 1.3:1. The commonest cause of admission was perinatal asphyxia (23.0%), prematurity (21.4%) and neonatal sepsis (18.5%). The mortality rate was 13.2% were the commonest causes of death been prematurity (26.2%), perinatal asphyxia (17.8%) and neonatal sepsis (7.8%). Discharge against medical advice (DAMA) rate of is 6.7%. Conclusions: The study showed that prematurity, perinatal asphyxia and neonatal sepsis remain the commonest cause of admissions and death in our SCBU.